\ \
The equation is
According to addition property of equality: If a = b then a + c = b + c.
\ (Add 3r to each side)
(Subtract:
)
\ \
According to subtraction property of equality: If a = b then a – c = b – c.
\ (Subtract 17 from each side)
(Apply commutative property)
(Subtract:
)
(Divide each side by -3)
(Cancel common terms) \ \
\
\
Verify:
\To check the solution, substitute in original equation.
\ \
(Cancel common terms)
(Multiply:
)
(Add:
,)
Compare the values, the equation is true. The solution is .
\ \
The value of .